Atypical mandibular metastasis as the first presentation of a colorectal cancer. (4th June 2018) - Salvador, João Cunha; Rosa, Duarte; Rito, Miguel; Borges, Alexandra
Abstract : We describe a case of a 70-year-old man presenting with a mandibular metastasis as the first sign of a mucinous adenocarcinoma of the rectum. After 6 months of a protracted toothache, the patient presented with a palpable mandibular mass and trismus, precluding adequate clinical evaluation. A CT scan was performed, and imaging findings suggested an aggressive primary jawbone tumour, most likely an osteosarcoma. However, biopsy and further patient's management proved to be a metastasis. Metastasis to the oral cavity account for only 1%–3% of all malignant oral tumours, and the mandible is the most frequent site. Clinical presentation can be quite variable, and most often a primary malignancy is already known. Jawbone metastases are a sign of disseminated malignant neoplasms, with poor prognosis and usually an indication for palliative therapy.